Anti-fungal effects of Essential Oil and Nano-emulsion of some Medicinal Plants on the Human Pathogenic Fungus Candida albicansAntifungal potential of Essential oil Nanoemulsions…: Antifungal potential of Essential oil Nanoemulsions… - Khoshbakhtt, Shabnam; Taliei, Fakhtak; Ghasemi Bezdi, Kamal; Gharakhlo, Shima (Iranian Journal of Pharmaceutical Sciences, 2023)
Interest in essential oils is continuously increasing due to their biological activities in various fields, from pharmaceuticals to food and agriculture. Essential oil is unstable and hydrophobic under normal storage conditions. Thus, it can quickly lose its anti-fungal and antibacterial activity. The new method of nano-emulsion production has been proposed as an effective solution to increase their stability and activity. In this study, the nano-emulsions of Myrthus communis, Rosmarinus officinalis, and Eryngium campestre essential oils were formulated using different proportions and evaluated on Candida albicans. Nano-emulsions were prepared using an ultrasonic method, and the field emission scanning electron microscopy (FESEM) apparatus determined the size of the prepared nano-emulsion particles. The dilution method determined the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC). Also, the bioassay of plant compounds was investigated using the agar well diffusion method. Mean droplet size of M. communis, R. officinalis, and E. campestre nanoparticles were reported in 200-500, 100-200, and 200-300 nm, respectively. The lowest MIC value was obtained for the M. communis (12.5) and R. officinalis (12.5) nano-emulsion. The activity of the essential oil and nano-emulsion of the tested plants against C. albicans was confirmed with an inhibition zone diameter of 3.9-27.5 mm. Examining the time growth curve of C. albicans showed that nano-emulsions were significantly more effective on the fungal pathogen than essential oils. Results show that using nano-emulsions increases the antimicrobial properties of essential oils from medicinal plants.